ANALISIS PREFERENSI KONSUMEN TERHADAP BUAH APEL LOKAL DAN APEL IMPOR PADA BUMI NYIUR SWALAYAN DI KOTA PALU - Harisal, Harisal; Effendy, Effendy; Howara, Dafina (AGROTEKBIS, 2018)
The purpose of this research is to know the characteristics and preferences of consumers in buying local apples and import apples at Bumi Nyiur Swalayan. This research was carried out at Bumi Nyiur Supermarket that located in S. Parman street Palu City. The location determination is done deliberately (Purposive) with a total of 50 respondents were by technical of Accidental Random Sampling. The analysis used the analysis chi square and analysis multiatribut fishbein. The analysis show that attribute into preferences of consumers of local apples at a price Rp. 30,000 - Rp. 39,999/kilogram, has a sweet taste slightly acid, greenish yellow colour, medium size, crunchy texture watery. On an import apples, attribute into preferences of consumers is a price > Rp. 50.000/ kilogram, sweet taste, reddish yellow colour, big size, crunchy texture watery. The attribute that most consumers consider the purchase decision-making of local apples in a row from the highest to the lowest is price, size, texture, taste and colour. Unlike the import apples which the value attitudes toward the attributes that most consumer consider in a row from the highest to the lowest is taste, size, price, and colour.